PENERJEMAHAN KETERAMPILAN BERBAHASA YANG BERHUBUNGAN DENGAN PROSES PENGEMBANGAN BAHASA SEBUAH TAWARAN KEWIRAUSAHAAN DALAM KEGIATAN BERBAHASA - Ingrid Veronica Kusumawardani (Politeknik Negeri Media Kreatif, 2018)
This journal contains argumentation of researcher’s idea on language skill which not only have an influence to language development but also entrepreneur’s activity which can be executed by any person who wants to be a translator. Considering that translation is a language activity having opportunity to produce income for translator. Researcher intensively executes the research towards translation process with literature review and data analysis to gain validated data that can be accounted for because it is done in accordance with carefull and detailed observation. Researcher used descriptive methodology. In implementation, researcher used literature review for the data used resourcing from literature data, then the data analysis of this journal is qualitative analysis that is analysis of contain to data. Therefore the data was analyzed based on the level of its linkage to the problem. As for the discussion of this journal contains exposure on basis of researcher’s understanding to some theories which researcher is as actor of language and entrepreneur in the field of language. In the discussion, researcher explained what needed skills are by a translator, how the relationship between translation and language development, then how big the ability of translation can be used as one of language activities which can produce income through the language activity. Therefore in the end of discussion shall be delivered all goals of this journal. Next, in conclusion and suggestion part, researcher would deliver the observation and discussion, then followed by suggestion in line with the conlucion